The impact of IPPK and IUPHHK on community economies in Malinau district - Affandi, O. (Center for International Forestry Research, 2006)
Regional autonomy (OTDA) has opened up the opportunity for districts to manage their forest resources (SDH), however, the division of authority between district and central governments remains unclear. So, how and to what extent can this opportunity improve community livelihoods? For the research presented here, data was collected to answer these questions for the case of Malinau District, where, as in other forest-rich regions, decentralization has been marked with regional government (Pemda) policies granting IPPK (timber extraction and utilization permits) and IUPHHK (forest timber product exploitation permits, better known as mini HPHs). The research, conducted in the three villages of Long Pangin, Laban Nyarit, and Langap between April and June 2004, show these policies have not had the desired results. Communities’ lack of capital and technical capacity led them to give their permits to people with better access to capital. Communities only received fees. Communities’ lack of access to information and support when negotiating with these entrepreneurs resulted in agreements where the entrepreneurs enjoyed the greatest benefits while communities were left with very little.